Silicon-carbon negative electrode material, negative electrode sheet and secondary battery

CN117174862BActive Publication Date: 2026-10-23JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311204139.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2026-10-23
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

但到目前为止,导电性能较差,它的仍然受到在放电下更高DCR,放电性能较差的困扰

Benefits of technology

[0034](1)本申请中,短时加热碳化(即一次加热碳化)混合金属元素的第一碳源,得到低碳化颗粒(掺杂金属元素的硬碳内核)具有更多的短程碳层,导电性更高。利用含氮/磷化合物与第二碳源(煤沥青/焦炭/石油沥青/针状焦/等方焦/重质油及其组合物)包覆低碳化颗粒,二次加热碳化形成含氮/磷的软碳包覆层,低碳化颗粒与含氮/磷的软碳包覆层形成双掺杂区域,配合碳沉积层,制备出的硅碳负极材料具有较低的粉末电阻。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117174862B_ABST
    Figure CN117174862B_ABST
Patent Text Reader

Abstract

The application discloses a silicon-carbon negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: uniformly mixing a first carbon source and a metal element or a metal compound, and performing primary heating and carbonization to obtain low-carbonized particles doped with the metal element; after surface activation treatment, the low-carbonized particles are placed in a reaction device to introduce a silicon-containing gas, so that silicon is deposited in pores of the low-carbonized particles doped with the metal element, and a silicon-carbon matrix is obtained; the silicon-carbon matrix, a nitrogen / phosphorus-containing compound and a second carbon source are uniformly mixed, and secondary heating and carbonization are performed to form a soft carbon coating layer containing nitrogen / phosphorus on the surface of the silicon-carbon matrix, ball milling and screening are performed to obtain a silicon-carbon main material; a carbon-containing gas is introduced to form a carbon deposition layer on the surface of the silicon-carbon main material, and the silicon-carbon negative electrode material is obtained. The silicon-carbon negative electrode material prepared by the application has a low powder resistance, so that a secondary battery using the silicon-carbon negative electrode material has a low DCR and good rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a silicon-carbon anode material, an anode sheet, and a secondary battery. Background Technology

[0002] Lithium-ion batteries (LIBs) have become the primary chemical power source due to their advantages in energy density, power density, and cycle life. Regarding anode materials, silicon anode materials are considered the most promising alternative for next-generation lithium-ion battery anodes. They possess a theoretical specific capacity nearly 10 times that of traditional graphite anode materials (4200 mAh / g); furthermore, silicon is widely available, making it ideal for large-scale production and application.

[0003] Deposited silicon-carbon anode materials are a promising type of silicon anode material for lithium-ion batteries. Nanoscale silicon clusters are deposited and dispersed within carbon materials, providing high reversible capacity (>1500 mAh / g). During the first cycle, lithium silicon forms in situ within the silicon matrix and is surrounded by the porous carbon structure of the carbon material. This serves a dual purpose: buffering volume expansion and isolating the nano-silicon clusters from direct contact with the electrolyte. This reduces the negative effects of volume expansion during lithiation and excessive electrolyte consumption, thus improving battery lifespan. Therefore, deposited silicon-carbon anode materials have significant advantages in electrochemical performance and are more in line with the commercialization direction of silicon-based materials. However, to date, their conductivity is relatively poor, and they are still plagued by higher discharge coefficients (DCR) and poor discharge performance.

[0004] Therefore, it is still necessary to explore effective methods to simultaneously achieve the two goals of lower discharge rate coefficient (DCR) and improved discharge rate performance of deposited silicon-carbon anode materials. Summary of the Invention

[0005] This invention provides a silicon-carbon anode material, an anode sheet, and a secondary battery, enabling the secondary battery containing the silicon-carbon anode material to exhibit a lower discharge rate coefficient (DCR) and a higher discharge rate performance.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0007] The first aspect of the present invention provides a silicon-carbon anode material, wherein the silicon-carbon anode material has a core-shell structure, comprising, from the inside out, a hard carbon core, a soft carbon coating layer, and a carbon deposition layer, wherein the hard carbon core is doped with metal elements and silicon particles are embedded in the pores of the hard carbon core, and the soft carbon coating layer is doped with nitrogen / phosphorus elements.

[0008] In one embodiment of the present invention, the hard carbon core has a particle size of 0.1 to 60 μm, the soft carbon coating layer has a thickness of 0.002 to 1.5 μm, and the carbon deposition layer has a thickness of 0.002 to 0.4 μm.

[0009] In one embodiment of the present invention, the silicon-carbon anode material has multiple pores distributed inside, and the diameter of the pores is 0.4 to 300 nm.

[0010] In one embodiment of the present invention, the proportion of pores with a diameter of 0 to 2 nm in the silicon-carbon anode material is denoted as PD2, the proportion of pores with a diameter of 0 to 10 nm is denoted as PD1, and PD2 / PD1 = 50 to 98%.

[0011] In one embodiment of the present invention, the silicon-carbon anode material has a carbon content of 15-65%, a silicon content of 15-65%, and a total carbon and silicon content of 80-99%, and an oxygen content of 0.1-8%.

[0012] A second aspect of this invention provides a method for preparing a silicon-carbon anode material, comprising the following steps:

[0013] The first carbon source is mixed evenly with a metal element or metal compound, and then heated and carbonized in one step to obtain low-carbon particles doped with metal elements.

[0014] The low-carbon particles doped with metal elements are subjected to surface activation treatment. The surface-activated low-carbon particles are placed in a reaction device, a silicon-containing gas is introduced, and the device is heated to cause silicon particles to be deposited in the pores of the low-carbon particles doped with metal elements, thereby obtaining a silicon-carbon matrix.

[0015] The silicon-carbon matrix, nitrogen / phosphorus compound and second carbon source are mixed evenly, and then carbonized by secondary heating to form a nitrogen / phosphorus soft carbon coating layer on the surface of the silicon-carbon matrix. The silicon-carbon main material is obtained by ball milling and sieving.

[0016] The silicon-carbon host material is placed in a reaction apparatus at a certain temperature, and a carbon-containing gas is introduced to form a carbon deposition layer on the surface of the silicon-carbon host material, thereby obtaining the silicon-carbon anode material.

[0017] In one embodiment of the present invention, the first carbon source is selected from one or more of polyvinyl alcohol, phenolic resin, epoxy resin, polyoxyethylene, furfural resin, and urea-formaldehyde resin.

[0018] In one embodiment of the present invention, the first carbon source is in a molten state.

[0019] In one embodiment of the present invention, the elemental metal or metal compound is selected from one or more of butyllithium, phenyllithium, lithium silicate, lithium oxalate, lithium carbonate, lithium metal, magnesium silicate, lithium silicate, aluminum silicate, lithium aluminate, magnesium metal, aluminum metal, magnesium hydroxide, aluminum hydroxide, aluminum carbonate, aluminum titanate, magnesium titanate, magnesium oxide, aluminum oxide, titanium oxide, magnesium chloride, aluminum chloride, titanium chloride, magnesium sulfate, magnesium nitrate, aluminum sulfate, aluminum nitrate, titanium sulfate, lithium borate, sodium borate, magnesium borate, aluminum borate, tin powder, tin oxalate, tin carbonate, stannous sulfate, stannous chloride, dibutyltin, and dimethyltin.

[0020] In one embodiment of the present invention, the temperature of the primary heating carbonization is 400-900°C and the time is 1-6 hours.

[0021] In one embodiment of the present invention, the step of surface activation treatment of the low-carbon particles doped with metal elements specifically involves: mixing the low-carbon particles, activator and solvent in a mass ratio of 1:(0.05~0.4):(5~20) to obtain a mixed solution, adding ammonia water to adjust the pH value of the mixed solution to 9~12.5, treating at 40~80℃ for 1~10h, filtering and drying to obtain the activated low-carbon particles.

[0022] In one embodiment of the present invention, the activator is selected from one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide.

[0023] In one embodiment of the present invention, the silicon-containing gas is composed of a gaseous silicon source and an inert gas, wherein the silicon source is selected from one or more of silane, silane, propane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

[0024] In one embodiment of the present invention, in the step of heating to deposit silicon particles in the pores of the low-carbon particles doped with metal elements, the heating temperature is 300 to 980°C and the deposition time is 20 min to 8 h.

[0025] In one embodiment of the present invention, the second carbon source is selected from one or more of coal tar pitch, coke, petroleum pitch, needle coke, isotropic coke, and heavy oil.

[0026] In one embodiment of the present invention, the second carbon source is in a molten state.

[0027] In one embodiment of the present invention, the nitrogen / phosphorus compound is selected from one or more of ammonium phosphate, ammonium oxalate, ammonium hydrogen phosphate, phosphoric acid, melamine, ammonium tripolyphosphate, sodium tripolyphosphate, ammonium pyrophosphate, pyrophosphate, and ammonium citrate.

[0028] In one embodiment of the present invention, the temperature of the secondary heating carbonization is 450-800°C and the time is 2-12 hours.

[0029] In one embodiment of the present invention, in the step of placing the silicon-carbon host material in a reaction apparatus at a certain temperature and introducing a carbon-containing gas to form a carbon deposition layer on the surface of the silicon-carbon host material, the temperature is 300-800°C and the time for introducing the carbon-containing gas is 20 min-10 h.

[0030] A third aspect of the present invention provides a negative electrode sheet, comprising the silicon-carbon negative electrode material described in the first aspect or the silicon-carbon negative electrode material prepared by the preparation method described in the second aspect.

[0031] In one embodiment of the present invention, the negative electrode sheet includes a current collector and a negative electrode active material layer coated on the surface of the current collector.

[0032] A fourth aspect of the present invention provides a secondary battery comprising the silicon-carbon anode material described in the second aspect or the anode sheet described in the third aspect.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) In this application, a first carbon source containing mixed metal elements is carbonized by short-time heating (i.e., single-stage heating carbonization) to obtain low-carbonized particles (hard carbon cores doped with metal elements) with more short-range carbon layers and higher conductivity. The low-carbonized particles are coated with nitrogen / phosphorus compounds and a second carbon source (coal tar pitch / coke / petroleum pitch / needle coke / isocubic coke / heavy oil and their combinations), and a second heating carbonization is performed to form a nitrogen / phosphorus soft carbon coating layer. The low-carbonized particles and the nitrogen / phosphorus soft carbon coating layer form a double-doped region. Combined with a carbon deposition layer, the prepared silicon-carbon anode material has a low powder resistance.

[0035] (2) Activation of low-carbon particles through surface pores increases the porosity of hard carbon particles, which is beneficial for the uniform dispersion of silicon particles within the low-carbon particles. Simultaneously, the large number of pores increases the specific surface area of ​​the low-carbon particles, improving silicon deposition. Furthermore, activation of low-carbon particles through surface pores allows for a tighter bond between the soft carbon coating layer and the silicon-carbon matrix (a hard carbon core with silicon particles embedded in the pores), thereby reducing lithium-ion interfacial transport resistance and improving the material's ion diffusion capability. Through increased bonding between the low-carbon particles, the nitrogen / phosphorus-containing soft carbon coating layer, and the carbon deposition layer's internal and external surfaces, and different doping methods, the supporting structure and material conductivity are synergistically improved, effectively constructing a conductive network. This results in the silicon-carbon anode material of this application exhibiting low DCR and excellent rate performance. Attached Figure Description

[0036] Figure 1This is a schematic diagram of the structure of silicon-carbon anode material, where 1 is the hard carbon core, 2 is the soft carbon coating layer, and 3 is the carbon deposition layer. Detailed Implementation

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. "Comprising" or "containing" as used herein means that it may include or contain other components in addition to the stated components. "Comprising" or "containing" as used herein may also be replaced with the closed form "is" or "consisting of".

[0038] As described in the background section, silicon-carbon anode materials have become the most promising alternative materials for next-generation lithium-ion battery anodes due to their advantages such as high theoretical specific capacity (4200 mAh / g) and wide availability of raw materials. However, silicon-carbon anode materials suffer from problems such as large volume expansion and poor conductivity. Therefore, developing low DCR and excellent rate performance remains a challenge for current silicon-carbon anode active materials.

[0039] To solve the above-mentioned technical problems, the present invention provides a silicon-carbon anode material, wherein the silicon-carbon anode material has a core-shell structure, and from the inside out are a hard carbon core, a soft carbon coating layer, and a carbon deposition layer. The hard carbon core is doped with metal elements, and silicon particles are embedded in the pores of the hard carbon core. The soft carbon coating layer is doped with nitrogen / phosphorus elements.

[0040] In one embodiment of the present invention, the hard carbon core has a particle size of 0.1 to 60 μm, the soft carbon coating layer has a thickness of 0.002 to 1.5 μm, and the carbon deposition layer has a thickness of 0.002 to 0.4 μm.

[0041] In one embodiment of the present invention, the silicon-carbon anode material has multiple pores distributed inside, and the diameter of the pores is 0.4 to 300 nm.

[0042] In one embodiment of the present invention, the proportion of pores with a diameter of 0 to 2 nm in the silicon-carbon anode material is denoted as PD2, the proportion of pores with a diameter of 0 to 10 nm is denoted as PD1, and PD2 / PD1 = 50 to 98%.

[0043] In one embodiment of the present invention, the silicon-carbon anode material has a carbon content of 15-65%, a silicon content of 15-65%, and a total carbon and silicon content of 80-99%, and an oxygen content of 0.1-8%.

[0044] In one embodiment of the present invention, the specific surface area of ​​the silicon-carbon anode material is 0.75–28 m². 2 / g.

[0045] In one embodiment of the present invention, the tap density of the silicon-carbon anode material is 0.6–1.6 m³ / s. 3 / g.

[0046] The embodiments of this invention provide a method for preparing a silicon-carbon anode material, comprising the following steps:

[0047] S1. Mix the first carbon source with a metal element or metal compound evenly, and then heat and carbonize it once to obtain low-carbon particles doped with metal elements.

[0048] S2. After surface activation treatment of the low-carbon particles doped with metal elements, the surface-activated low-carbon particles are placed in a reaction device, silicon-containing gas is introduced, and heating is performed to cause silicon particles to be deposited in the pores of the low-carbon particles doped with metal elements, thereby obtaining a silicon-carbon matrix.

[0049] S3. The silicon-carbon matrix, nitrogen / phosphorus compound and second carbon source are mixed evenly, and carbonized by secondary heating to form a nitrogen / phosphorus soft carbon coating layer on the surface of the silicon-carbon matrix. The silicon-carbon main material is obtained by ball milling and sieving.

[0050] S4. Place the silicon-carbon host material in a reaction apparatus at a certain temperature, introduce carbon-containing gas, and form a carbon deposition layer on the surface of the silicon-carbon host material to obtain the silicon-carbon anode material.

[0051] In one embodiment of the present invention, in step S1, the first carbon source is selected from one or more of polyvinyl alcohol, phenolic resin, epoxy resin, polyoxyethylene, furfural resin, and urea-formaldehyde resin.

[0052] In one embodiment of the present invention, in step S1, the first carbon source is in a molten state.

[0053] In one embodiment of the present invention, the first carbon source in the molten state is obtained by heating the first carbon source to 150-250°C. The first carbon source in the molten state can ensure the uniformity of mixing with elemental metals or metal compounds, thereby ensuring a uniform distribution of metal elements in the prepared low-carbonized particles.

[0054] In one embodiment of the present invention, in step S1, the elemental metal or metal compound is selected from one or more of butyllithium, phenyllithium, lithium silicate, lithium oxalate, lithium carbonate, lithium metal, magnesium silicate, lithium silicate, aluminum silicate, lithium aluminate, magnesium metal, aluminum metal, magnesium hydroxide, aluminum hydroxide, aluminum carbonate, aluminum titanate, magnesium titanate, magnesium oxide, aluminum oxide, titanium oxide, magnesium chloride, aluminum chloride, titanium chloride, magnesium sulfate, magnesium nitrate, aluminum sulfate, aluminum nitrate, titanium sulfate, lithium borate, sodium borate, magnesium borate, aluminum borate, tin powder, tin oxalate, tin carbonate, stannous sulfate, stannous chloride, dibutyltin, and dimethyltin.

[0055] In one embodiment of the present invention, in step S1, the temperature of the primary heating carbonization is 400–900°C, and the time is 1–6 hours. This primary heating carbonization is a short-duration process, resulting in low-carbon particles doped with metal elements that are rich in hydrogen and oxygen. This is because the short carbonization time leads to incomplete high-temperature carbonization, resulting in surface functional groups and in-plane defects that may exist on the particle surface. Carbon development is slow, and a relatively large amount of carbon, hydrogen, and oxygen remains. The low-carbon particles have more short-range carbon layers and higher conductivity.

[0056] In one embodiment of the present invention, step S2, the step of surface activation treatment of the low-carbon particles doped with metal elements, specifically involves: mixing the low-carbon particles, activator, and solvent at a mass ratio of 1:(0.05-0.4):(5-20) to obtain a mixed solution; adding ammonia water to adjust the pH value of the mixed solution to 9-12.5; performing surface activation treatment at 40-80°C for 1-10 hours; and filtering and drying to obtain the activated low-carbon particles. Surface activation treatment of the low-carbon particles doped with metal elements (hard carbon particles) increases the surface porosity of the hard carbon particles. A large number of pores can increase the specific surface area of ​​the low-carbon particles, and the external pores are more numerous than the internal ones, which is beneficial for silicon particles to enter the interior of the low-carbon particles during subsequent silicon deposition. The silicon particles can be more dispersed and avoid agglomeration.

[0057] In one embodiment of the present invention, in the step of surface activation treatment of the low-carbon particles doped with metal elements, the activator is selected from one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide.

[0058] In one embodiment of the present invention, in step S2, the silicon-containing gas is composed of a gaseous silicon source and an inert gas, wherein the silicon source is selected from one or more of silane, silane, propane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

[0059] In one embodiment of the present invention, in step S2, the step of heating to deposit silicon particles in the pores of the low-carbon particles doped with metal elements, the heating temperature is 300-980°C, and the deposition time is 20 min-8 h.

[0060] In one embodiment of the present invention, in step S2, the reaction device can be a fluidized bed or any other commonly used device in the art, which can introduce reaction gas at a certain temperature to achieve silicon deposition.

[0061] In one embodiment of the present invention, in step S3, the second carbon source is selected from one or more of coal tar pitch, coke, petroleum pitch, needle coke, isotropic coke, and heavy oil.

[0062] In one embodiment of the present invention, in step S3, the second carbon source is in a molten state.

[0063] In one embodiment of the present invention, the molten second carbon source is obtained by heating the second carbon source to 120–210°C. The molten second carbon source can form a uniform coating layer on the surface of the silicon-carbon matrix and ensure the uniformity of nitrogen / phosphorus doping.

[0064] In one embodiment of the present invention, in step S3, the nitrogen / phosphorus compound is selected from one or more of ammonium phosphate, ammonium oxalate, ammonium hydrogen phosphate, phosphoric acid, melamine, ammonium tripolyphosphate, sodium tripolyphosphate, ammonium pyrophosphate, pyrophosphate, and ammonium citrate.

[0065] In one embodiment of the present invention, in step S3, the temperature of the secondary heating carbonization is 450–800°C, and the time is 2–12 hours. After the low-carbonized particles undergo secondary heating carbonization, the residual carbon, hydrogen, and oxygen elements on their surface will vaporize and volatilize, and the porosity of the low-carbonized particle surface will further increase.

[0066] In one embodiment of the present invention, in step S4, the silicon-carbon host material is placed in a reaction device at a certain temperature, and a carbon-containing gas is introduced to form a carbon deposition layer on the surface of the silicon-carbon host material. The temperature is 300-800°C, and the time for introducing the carbon-containing gas is 20 min-10 h. The carbon-containing gas is selected from one or more of methane, ethane, propane, acetylene, propyne, butyne, and ethylene.

[0067] In one embodiment of the present invention, in step S4, the reaction device can be a fluidized bed or any other commonly used device in the art, which can introduce reaction gas at a certain temperature to achieve carbon deposition.

[0068] The present invention provides a negative electrode sheet comprising the above-mentioned silicon-carbon negative electrode material.

[0069] In one embodiment of the present invention, the negative electrode sheet includes a current collector and a negative electrode active material layer coated on the surface of the current collector.

[0070] In one embodiment of the present invention, the negative electrode active material layer of the negative electrode sheet contains the following components by mass percentage: 85-99.6% of negative electrode active material (including the above-mentioned silicon-carbon negative electrode material), 0.2-7% of conductive material, and 0.2-8.0% of binder.

[0071] In one embodiment of the present invention, the method for preparing the negative electrode sheet includes the following steps:

[0072] (1) Weigh the negative electrode active material (the mass ratio of silicon-carbon negative electrode material to graphite negative electrode material is 1-80:15-90), conductive material and binder material according to the mass ratio of each component in the negative electrode active material layer of the negative electrode sheet. Mix the negative electrode active material and conductive material for the first time to obtain a first mixture.

[0073] (2) The primary mixture prepared in step (1) is mixed with binder and water for a second time to obtain a secondary mixture. The solid content of the secondary mixture is 40-60% and the viscosity is 1-6 Pa·s.

[0074] (3) The secondary mixture prepared in step (2) is coated onto the negative electrode fluid, and after drying, first rolling, second rolling and slitting, the negative electrode sheet is obtained.

[0075] In one embodiment of the present invention, the conductive material is selected from one or more of conductive carbon black, acetylene black, graphite, graphene, carbon microwires, carbon nanowires, carbon microtubes, and carbon nanotubes.

[0076] In one embodiment of the present invention, the adhesive is selected from one or more of polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, methacrylamide, polyacrylic acid, lithium polyacrylate, polyacrylamide, polyimide, polyacrylate, styrene-butadiene rubber, sodium alginate, polyethylene glycol, and guar gum.

[0077] In one embodiment of the present invention, the stirring speed for the first stirring is preferably 200-1500 r / min, and the stirring time is preferably 5-30 min.

[0078] In one embodiment of the present invention, the rotation speed of the second stirring is preferably 100-3000 r / min, and the time is preferably 5 min-10 h.

[0079] In one embodiment of the present invention, the solid content in the secondary mixture is more preferably 45-55%, and the viscosity is more preferably 2.5-4 Pa·s.

[0080] In one embodiment of the present invention, the negative electrode current collector is selected from one or more of copper foil, porous copper foil, foamed nickel / copper foil, nickel-plated copper foil, carbon-coated copper foil, nickel foil, and composite current collector.

[0081] In one embodiment of the present invention, the pressure of the first rolling is 10-80T, controlling the negative electrode sheet to reach 40-80% of the required compaction density; the pressure of the second rolling is 10-80T, controlling the negative electrode sheet to reach 80-110% of the required compaction density. The required compaction density and thickness are achieved through two rolling processes to ensure that the subsequent electrode sheet rebound thickness is within an appropriate range.

[0082] In one embodiment of the present invention, the compacted density of the slit negative electrode sheet is between 1.40 and 1.80 g / cm³. 3 The preferred value is 1.55–1.65 g / cm³. 3 The thickness is 35–500 μm, preferably 60–180 μm.

[0083] The present invention provides a secondary battery comprising the aforementioned silicon-carbon anode material or anode sheet.

[0084] In one embodiment of the present invention, the secondary battery comprises a positive electrode, a negative electrode, a separator, and an electrolyte; wherein, the positive electrode active material in the positive electrode may be one or more of lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium vanadium fluorophosphate, lithium iron manganese fluorophosphate, lithium nickel iron manganese oxide, lithium nickel copper manganese oxide, lithium nickel copper manganese iron oxide, lithium hexacyanide ferrite, lithium hexacyanide manganese oxide, lithium hexacyanide nickel oxide, lithium hexacyanide iron nickel oxide, lithium hexacyanide manganese nickel oxide, lithium hexacyanide iron manganese oxide, lithium titanium phosphate, and lithium titanium manganese phosphate; the separator may be a polymeric organic separator of at least one of polyethylene, polypropylene, polysulfonyl, polyacrylonitrile, polyvinyl alcohol, polyarylethersulfone, polyvinylidene fluoride, and polymalonic acid; the electrolyte may be formulated using conventional ratios in the art.

[0085] The present invention will be further described below with reference to specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the embodiments are not intended to limit the present invention.

[0086] Example 1

[0087] This embodiment relates to a method for preparing a silicon-carbon anode material, the specific steps of which are as follows:

[0088] 1.1 First doping: The first carbon source (phenolic resin) and the dopant (lithium aluminate) heated to 160℃ are mixed evenly at a mass ratio of 100:0.5, and then sent to a heating furnace for carbonization at 800℃ for 2 hours. After cooling, ball milling and sieving, particles with a size of 0.1~240μm are obtained, which are low-carbonized particles.

[0089] 1.2 Silicon Deposition: The surface pores of the low-carbon particles were activated by mixing the low-carbon particles and the activator (cetyltrimethylammonium bromide) at a ratio of 1:0.12 in a reactor. Ten times the mass of water (propanol / ethanol) was added to the low-carbon particles, and ammonia was added dropwise until the pH of the mixture reached 11. Surface pores were activated at 55°C for 3 hours, followed by centrifugation, filtration, and drying to obtain the activated low-carbon particles. The activated low-carbon particles were then fed into a fluidized bed at a temperature controlled at 550°C. Argon gas was introduced as a protective gas to purge air, and the fluidized bed pressure was 100 Pa. A mixed silicon source (silane source and argon gas flow ratio of 5:2) was introduced to deposit silicon for 1.5 hours to obtain a silicon-carbon matrix.

[0090] 1.3 Second doping: The silicon-carbon matrix, dopant (ammonium phosphate), and petroleum asphalt heated to 180°C are mixed evenly (mass ratio of 95:1.5:2.5), and then sent to a heating furnace under nitrogen atmosphere at 650°C for 6 hours for carbonization, followed by cooling, ball milling, sieving, and demagnetization to obtain particles with a size of 0.1-60μm, which is the surface-doped silicon-carbon matrix (i.e., the main body);

[0091] 1.4 Carbon deposition: The temperature of the fluidized bed is controlled at 500℃, and carbon-containing gas (acetylene) is introduced to perform deposition for 40 minutes (i.e., the surface layer), thus obtaining the doped silicon-carbon anode material.

[0092] Example 2

[0093] This embodiment relates to a method for preparing a silicon-carbon anode material, the specific steps of which are as follows:

[0094] 1.1 First doping: The first carbon source (phenolic resin) and the dopant (lithium aluminate) heated to 160℃ are mixed evenly at a mass ratio of 100:0.5, and then sent to a heating furnace for carbonization at 800℃ for 2 hours. After cooling, ball milling and sieving, particles with a size of 0.1~240μm are obtained, which are low-carbonized particles.

[0095] 1.2 Silicon Deposition: The surface pores of the low-carbon particles were activated by mixing the low-carbon particles and the activator (cetyltrimethylammonium bromide) at a ratio of 1:0.12 in a reactor. Ten times the mass of water (propanol / ethanol) was added to the low-carbon particles, and ammonia was added dropwise until the pH of the mixture reached 11. Surface pores were activated at 55°C for 3 hours, followed by centrifugation, filtration, and drying to obtain the activated low-carbon particles. The activated low-carbon particles were then fed into a fluidized bed at a temperature controlled at 550°C. Argon gas was introduced as a protective gas to purge air, and the fluidized bed pressure was 100 Pa. A mixed silicon source (silane source and argon gas flow ratio of 5:2) was introduced to deposit silicon for 1.5 hours to obtain a silicon-carbon matrix.

[0096] 1.3 Second doping: The silicon-carbon matrix, dopant (ammonium phosphate), and petroleum asphalt heated to 180°C are mixed evenly (mass ratio of 95:2.0:2.5), and then sent to a heating furnace under nitrogen atmosphere at 650°C for 6 hours for carbonization, followed by cooling, ball milling, sieving, and demagnetization to obtain particles with a size of 0.1-60μm, which is the surface-doped silicon-carbon matrix (i.e., the main body);

[0097] 1.4 Carbon deposition: The temperature of the fluidized bed is controlled at 500℃, and carbon-containing gas (acetylene) is introduced to perform deposition for 40 minutes (i.e., the surface layer), thus obtaining the doped silicon-carbon anode material.

[0098] Example 3

[0099] This embodiment relates to a method for preparing a silicon-carbon anode material, the specific steps of which are as follows:

[0100] 1.1 First doping: The first carbon source (phenolic resin) and the dopant (lithium aluminate) heated to 160℃ are mixed evenly at a mass ratio of 100:0.5, and then sent to a heating furnace for carbonization at 850℃ for 2 hours. After cooling, ball milling and sieving, particles with a size of 0.1~240μm are obtained, which are low-carbonized particles.

[0101] 1.2 Silicon Deposition: The surface pores of the low-carbon particles were activated by mixing the low-carbon particles and the activator (cetyltrimethylammonium bromide) at a ratio of 1:0.12 in a reactor. Ten times the mass of water (propanol / ethanol) was added to the low-carbon particles, and ammonia was added dropwise until the pH of the mixture reached 11. Surface pores were activated at 55°C for 3 hours, followed by centrifugation, filtration, and drying to obtain the activated low-carbon particles. The activated low-carbon particles were then fed into a fluidized bed at a temperature controlled at 550°C. Argon gas was introduced as a protective gas to purge air, and the fluidized bed pressure was 100 Pa. A mixed silicon source (silane source and argon gas flow ratio of 5:2) was introduced to deposit silicon for 1.5 hours to obtain a silicon-carbon matrix.

[0102] 1.3 Second doping: The silicon-carbon matrix, dopant (ammonium phosphate), and petroleum asphalt heated to 180°C are mixed evenly (mass ratio of 95:2.5:2.5), and then sent to a heating furnace under nitrogen atmosphere at 750°C for 6 hours for carbonization, followed by cooling, ball milling, sieving, and demagnetization to obtain particles with a size of 0.1-60 μm, which is the surface-doped silicon-carbon matrix (i.e., the main body);

[0103] 1.4 Carbon deposition: The temperature of the fluidized bed is controlled at 500℃, and carbon-containing gas (acetylene) is introduced to perform deposition for 40 minutes (i.e., the surface layer), thus obtaining the doped silicon-carbon anode material.

[0104] Example 4

[0105] This embodiment relates to a method for preparing a silicon-carbon anode material, the specific steps of which are as follows:

[0106] 1.1 First doping: The first carbon source (epoxy resin) and the dopant (aluminum borate) heated to 160℃ are mixed evenly at a mass ratio of 100:0.1, and then sent to a heating furnace for carbonization at 800℃ for 2 hours. After cooling, ball milling and sieving, particles with a size of 0.1~240μm are obtained, which are low-carbonized particles.

[0107] 1.2 Silicon Deposition: Surface porosity activation treatment was performed on the low-carbon particles. The low-carbon particles and activator (cetyltrimethylammonium bromide) were mixed in a reactor at a ratio of 1:0.18. Water (propanol) with a mass equal to that of the low-carbon particles was added, and ammonia was added dropwise until the pH of the mixture reached 11. Surface porosity activation was performed at 55°C for 2 hours, followed by centrifugation, filtration, and drying to obtain activated low-carbon particles. The activated low-carbon particles were then fed into a fluidized bed. The temperature of the fluidized bed was controlled at 550°C, and argon gas was introduced to purge air. The fluidized bed pressure was 100 Pa. A mixed silicon source (silane source and argon gas flow ratio of 5:3) was introduced to deposit silicon for 2 hours to obtain a silicon-carbon matrix.

[0108] 1.3 Second doping: The silicon-carbon matrix, dopant (ammonium phosphate / sodium tripolyphosphate) and needle coke heated to 150°C are mixed evenly (mass ratio of 95:1.5:2.5), and then sent to a heating furnace under nitrogen atmosphere at 650°C for 4 hours for carbonization, followed by cooling, ball milling, sieving, and demagnetization to obtain particles with a size of 0.1-60μm, which is the surface-doped silicon-carbon matrix (i.e., the main body);

[0109] 1.4 Carbon deposition: The temperature of the fluidized bed is controlled at 550℃, and carbon-containing gas (acetylene) is introduced to perform deposition for 35 minutes (i.e., the surface layer), thus obtaining the doped silicon-carbon anode material.

[0110] Example 5

[0111] This embodiment relates to a method for preparing a silicon-carbon anode material, the specific steps of which are as follows:

[0112] 1.1 First doping: The first carbon source (epoxy resin) and the dopant (aluminum borate) heated to 160℃ are mixed evenly at a mass ratio of 100:0.15, and then sent to a heating furnace for carbonization at 800℃ for 2 hours. After cooling, ball milling and sieving, particles with a size of 0.1~240μm are obtained, which are low-carbonized particles.

[0113] 1.2 Silicon Deposition: Surface porosity activation treatment was performed on the low-carbon particles. The low-carbon particles and activator (cetyltrimethylammonium bromide) were mixed in a reactor at a ratio of 1:0.18. Water (propanol) with a mass equal to that of the low-carbon particles was added, and ammonia was added dropwise until the pH of the mixture reached 11. Surface porosity activation was performed at 55°C for 2 hours, followed by centrifugation, filtration, and drying to obtain activated low-carbon particles. The activated low-carbon particles were then fed into a fluidized bed. The temperature of the fluidized bed was controlled at 550°C, and argon gas was introduced to purge air. The fluidized bed pressure was 100 Pa. A mixed silicon source (silane source and argon gas flow ratio of 5:3) was introduced to deposit silicon for 2 hours to obtain a silicon-carbon matrix.

[0114] 1.3 Second doping: The silicon-carbon matrix, dopant (sodium tripolyphosphate), and needle coke heated to 150°C are mixed evenly (mass ratio of 95:2.0:2.5), and then sent to a heating furnace under nitrogen atmosphere at 650°C for 4 hours for carbonization. After cooling, ball milling, sieving, and demagnetization, particles with a size of 0.1-60 μm are obtained, which are the surface-doped silicon-carbon matrix (i.e., the main body).

[0115] 1.4 Carbon deposition: The temperature of the fluidized bed is controlled at 550℃, and carbon-containing gas (acetylene) is introduced to perform deposition for 35 minutes (i.e., the surface layer), thus obtaining the doped silicon-carbon anode material.

[0116] Comparative Example 1

[0117] This comparative example relates to the preparation of a silicon-carbon anode material, which differs from Example 1 in that: no dopant (lithium aluminate) is added in step 1.1, and no aluminum or lithium elements are doped in the low-carbon particles.

[0118] Comparative Example 2

[0119] This comparative example relates to the preparation of a silicon-carbon anode material. The difference from Example 1 is that no dopant (ammonium phosphate) was added in step 1.2, and the soft carbon coating layer of the silicon-carbon matrix does not contain nitrogen or phosphorus elements.

[0120] Comparative Example 3

[0121] This comparative example relates to the preparation of a silicon-carbon anode material. The difference from Example 1 is that the carbonization time in step 1.1 is 12 hours, that is, carbonization is carried out at 800°C for 12 hours under long-term heating.

[0122] Comparative Example 4

[0123] This comparative example relates to the preparation of a silicon-carbon anode material, which differs from Example 1 in that the low-carbon particles were not subjected to surface pore activation.

[0124] Application and performance testing

[0125] 1. Application of silicon-carbon anode materials in lithium-ion batteries

[0126] Using the silicon-carbon anode material prepared in the above embodiments and comparative examples as the anode active material, anode sheets were prepared and lithium-ion secondary batteries were assembled. The specific preparation process is as follows:

[0127] Negative electrode sheet: First mixing: 1.44 kg of negative electrode material (mass ratio of silicon-carbon negative electrode material to graphite negative electrode material is 10:90) and 0.0225 kg of conductive material (90% carbon black + 10% carbon nanotubes) are placed in the mixing tank of a mixer and dry-mixed at 1500 r / min for 30 min to obtain a mixture; Second mixing: 0.375 kg of binder material (50% carboxymethyl cellulose + 50% polyacrylic acid) and 1.5 kg of deionized water are added to a container, the solid content is 50%, and the viscosity is adjusted to 3 Pa·s to obtain a mixed negative electrode slurry. The mixed negative electrode slurry is coated on carbon-coated copper foil, dried at 95℃, rolled once, rolled twice, and slit to obtain the silicon-carbon negative electrode sheet.

[0128] Positive electrode sheet: Lithium nickel cobalt manganese oxide, conductive carbon black, and PVDF binder are mixed in a mass ratio of 97.2:1.5:1.3. The mixture is then coated onto a carbon current collector using NMP as a solvent. After drying, rolling, cutting, and slitting, the positive electrode sheet is obtained.

[0129] A bare cell is obtained by sequentially stacking and winding a positive electrode sheet, a polyethylene separator, and a silicon-carbon negative electrode sheet. The electrode tabs are then ultrasonically welded. The bare cell is placed in a battery casing, dried at 105°C to remove moisture, and then injected with an electrolyte (1.0M LiPF6 (dispersed in a 1:1 volume ratio of ethylene carbonate and diethyl carbonate, with 5% fluoroethylene carbonate added) into the battery casing and encapsulated to obtain a lithium-ion secondary battery.

[0130] 2. Performance Testing

[0131] (1) Powder resistance test: The powder resistance of the negative electrode materials of Examples 1 to 5 and Comparative Examples 1 to 4 was tested using the four-probe method of the powder resistance test system (test conditions: pressure 180MPa, 25℃, relative humidity 10%).

[0132] (2) Electrical performance test: ① Formation and constant capacity: The secondary electrical devices of Examples 1 to 5 and Comparative Examples 1 to 4 were first charged at 0.02C at 45°C to a cutoff voltage of 3.7V, left to stand for 24 hours, and then charged at 0.5C to a cutoff voltage of 4.25V (4.25V constant voltage charging current < 0.05C); discharged at 1C to 2.8V, left to stand for 30 minutes, and then discharged at 0.1C to 2.8V. ② Electrochemical tests were conducted using the Blue Electric multi-channel electrochemical testing system: discharge at room temperature to 20% SOC at 1.0C, and test the discharge DCR of Examples 1-5 and Comparative Examples 1-4 at 20% SOC; then charge at 1.0C to the cutoff voltage of 4.25V (4.25V constant voltage charging current < 0.05C), and discharge at 1.0C, 1.5C, and 2.0C to 2.8V, calculating the discharge ratios of 1.5C and 2.0C (1.5C discharge ratio = 1.5C discharge quantity / 1.0C discharge quantity * 100%, 2.0C discharge ratio = 1.5C discharge quantity / 2.0C discharge quantity * 100%).

[0133] The results of the powder resistance test of the above negative electrode material and the electrical performance test of the secondary battery are shown in Table 1 below:

[0134] Table 1. Powder resistance and electrical performance test results of the negative electrode materials in Examples 1-5 and Comparative Examples 1-4, and the secondary batteries.

[0135]

[0136] As shown in the table above, treatments such as doping the hard carbon core with metal elements, doping the soft carbon coating with nitrogen and phosphorus elements, increasing the surface porosity of low-carbon particles through a single short-time carbonization followed by a secondary carbonization, and activating the surface porosity of low-carbon particles can improve the ion diffusion capability and conductivity of silicon-carbon anode materials, thereby improving powder resistance and thus improving the DCR and rate performance of secondary batteries. As shown in Examples 1 and Comparative Examples 1 and 2, when the low-carbon particles are not doped with metal elements or the soft carbon coating is not doped with nitrogen and phosphorus elements, the powder resistance increases to varying degrees, thus affecting the DCR and rate performance. A comparison between Example 1 and Comparative Example 3 shows that a single carbonization at 800°C for 12 hours is too long, leading to complete carbon development of the low-carbon particles, resulting in reduced material conductivity, manifested as high powder resistance and increased DCR. As can be seen from the comparison between Example 1 and Comparative Example 4, the low-carbon particles did not undergo surface pore activation, which is not conducive to the tight bonding between the external soft carbon region and the silicon-carbon matrix, reducing the lithium-ion interface transport resistance and improving the ion diffusion capacity of the material, thereby causing an increase in DCR.

[0137] In summary, the silicon-carbon anode material prepared using this application is beneficial to improving the material's conductivity and ion conduction performance, thereby enabling secondary batteries containing this silicon-carbon anode material to have lower DCR and excellent rate performance.

[0138] The embodiments described above are merely preferred examples to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A method for preparing a silicon-carbon anode material, characterized in that, The silicon-carbon anode material has a core-shell structure, consisting of a hard carbon core, a soft carbon coating layer, and a carbon deposition layer from the inside out. The hard carbon core is doped with metal elements, and silicon particles are embedded in the pores of the hard carbon core. The soft carbon coating layer is doped with nitrogen / phosphorus elements. The preparation method includes the following steps: The first carbon source is mixed evenly with a metal element or metal compound, and then heated and carbonized in one step to obtain low-carbon particles doped with metal elements. The low-carbon particles doped with metal elements are subjected to surface activation treatment. The surface-activated low-carbon particles are placed in a reaction device, a silicon-containing gas is introduced, and the device is heated to cause silicon particles to be deposited in the pores of the low-carbon particles doped with metal elements, thereby obtaining a silicon-carbon matrix. The silicon-carbon matrix, nitrogen / phosphorus compound and second carbon source are mixed evenly, and then carbonized by secondary heating to form a nitrogen / phosphorus soft carbon coating layer on the surface of the silicon-carbon matrix. The silicon-carbon main material is obtained by ball milling and sieving. The silicon-carbon host material is placed in a reaction apparatus at a certain temperature, and a carbon-containing gas is introduced to form a carbon deposition layer on the surface of the silicon-carbon host material, thereby obtaining the silicon-carbon anode material.

2. The preparation method according to claim 1, characterized in that, The hard carbon core has a particle size of 0.1~60μm, the soft carbon coating layer has a thickness of 0.002~1.5μm, and the carbon deposition layer has a thickness of 0.002~0.4μm.

3. The preparation method according to claim 1, characterized in that, The silicon-carbon anode material has multiple pores distributed inside, and the diameter of the pores is 0.4~300nm.

4. The preparation method according to claim 1, characterized in that, The proportion of pores with a diameter of 0~2nm in the silicon-carbon anode material is denoted as PD2, and the proportion of pores with a diameter of 0~10nm is denoted as PD1, and PD2 / PD1 = 50~98%.

5. The preparation method according to claim 1, characterized in that, The silicon-carbon anode material has a carbon content of 15-65%, a silicon content of 15-65%, and a total carbon and silicon content of 80-99%, with an oxygen content of 0.1-8%.

6. The preparation method according to claim 1, characterized in that, The first carbon source is selected from one or more of polyvinyl alcohol, phenolic resin, epoxy resin, polyoxyethylene, furfural resin, and urea-formaldehyde resin, and / or the first carbon source is in a molten state.

7. The preparation method according to claim 1, characterized in that, The metal element or metal compound is selected from one or more of butyllithium, phenyllithium, lithium silicate, lithium oxalate, lithium carbonate, lithium metal, magnesium silicate, lithium silicate, aluminum silicate, lithium aluminate, magnesium metal, aluminum metal, magnesium hydroxide, aluminum hydroxide, aluminum carbonate, aluminum titanate, magnesium titanate, magnesium oxide, aluminum oxide, titanium oxide, magnesium chloride, aluminum chloride, titanium chloride, magnesium sulfate, magnesium nitrate, aluminum sulfate, aluminum nitrate, titanium sulfate, lithium borate, sodium borate, magnesium borate, aluminum borate, tin powder, tin oxalate, tin carbonate, stannous sulfate, stannous chloride, dibutyltin, and dimethyltin.

8. The preparation method according to claim 1, characterized in that, The temperature for the first heating carbonization is 400~900℃, and the time is 1~6h.

9. The preparation method according to claim 1, characterized in that, The steps for surface activation treatment of the low-carbon particles doped with metal elements are as follows: the low-carbon particles, activator and solvent are mixed evenly in a mass ratio of 1:(0.05~0.4):(5~20) to obtain a mixed solution, ammonia water is added dropwise to adjust the pH value of the mixed solution to 9~12.5, and the solution is treated at 40~80℃ for 1~10h. The solution is then filtered and dried to obtain the activated low-carbon particles.

10. The preparation method according to claim 9, characterized in that, The activator is selected from one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide.

11. The preparation method according to claim 1, characterized in that, The silicon-containing gas is composed of a gaseous silicon source and an inert gas. The silicon source is selected from one or more of silane, silane, propane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

12. The preparation method according to claim 1, characterized in that, In the step of heating to deposit silicon particles into the pores of the low-carbon particles doped with metal elements, the heating temperature is 300~980℃ and the deposition time is 20min~8h.

13. The preparation method according to claim 1, characterized in that, The second carbon source is selected from one or more of coal tar pitch, coke, petroleum pitch, needle coke, isotropic coke, and heavy oil, and / or the second carbon source is in a molten state.

14. The preparation method according to claim 1, characterized in that, The nitrogen / phosphorus compound is selected from one or more of ammonium phosphate, ammonium oxalate, ammonium hydrogen phosphate, phosphoric acid, melamine, ammonium tripolyphosphate, sodium tripolyphosphate, ammonium pyrophosphate, pyrophosphate, and ammonium citrate.

15. The preparation method according to claim 1, characterized in that, The secondary heating carbonization temperature is 450~800℃, and the time is 2~12h.

16. The preparation method according to claim 1, characterized in that, In the step of placing the silicon-carbon host material in a reaction apparatus at a certain temperature and introducing a carbon-containing gas to form a carbon deposition layer on the surface of the silicon-carbon host material, the temperature is 300~800℃ and the time for introducing the carbon-containing gas is 20min~10h.

17. A negative electrode sheet, characterized in that, Including silicon-carbon anode materials prepared by the preparation method according to any one of claims 1-16.

18. A secondary battery, characterized in that, It includes the negative electrode sheet as described in claim 17.

Citation Information

Patent Citations

  • Lithium ion battery negative active material and preparation method thereof

    CN103956496A

  • Silicon-phosphorus co-doped hard carbon composite material and preparation method and application thereof

    CN114843480A

  • Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material

    CN114975945A